MVA-CoV2-S Vaccine Candidate Neutralizes Distinct Variants of Concern and Protects Against SARS-CoV-2 Infection in Hamsters - Boudewijns, Robbert; Pérez, Patricia; Lázaro-Frías, Adrián; Van Looveren, Dominique; Vercruysse, Thomas; Thibaut, Hendrik Jan; Weynand, Birgit; Coelmont, Lotte; Neyts, Johan; Astorgano, David; Montenegro, Dolores; Puentes, Eugenia; et al. (Frontiers in Immunology, 2022)
To control the COVID-19 pandemic and the emergence of different variants of concern (VoC), novel vaccines against SARS-CoV-2 are needed. In this study we report the potent immunogenicity and efficacy induced in hamsters by a vaccine candidate based on a modified vaccinia virus Ankara (MVA) vector expressing a human codon optimized full-length SARS-CoV-2 spike (S) protein (MVA-S). Immunization with one or two doses of MVA-S elicited high titers of S- and receptor binding domain (RBD)-binding IgG antibodies and neutralizing antibodies against parental SARS-CoV-2 and VoC alpha, beta, gamma, delta and omicron. After SARS-CoV-2 challenge, MVA-S-vaccinated hamsters showed a significant strong reduction of viral RNA and infectious virus in the lungs, compared to the MVA-WT control group. Moreover, a marked reduction in lung histopathology was also observed in MVA-S-vaccinated hamsters. These results favor the use of MVA-S as a potential vaccine candidate for SARS-CoV-2 in clinical trials.